Perbandingan Model Peluang Kegagalan Pada Sistem Pendingin Main engine Crew Boat 41 GT - Tasya Putri Lindyawati; Nurvita Arumsari; Aminatus Sa'diyah (Proceedings Conference on Marine Engineering and its Application, 2023)
Damage to the main engine is currently common, some cases result in sailing delays or eventhreaten human safety. Crew boat 41 GT is a ship that operates to transport crew or support offshore. Thus, it is necessary to pay attention to the maintenance of the main engine, especially the cooling sub-system which plays an important role in maintaining the working temperature of the main engine so as not to overheat. Therefore, it is necessary to predict the failure of the 41 GT crew boat main enginecooling sub-system components so that the right time can be determined to carry out maintenance onthese components before damage occurs. In this study, the prediction of reliability value was carriedout using qualitative (FMEA) and quantitative (theoretical and Monte carlo simulation) methods.FMEA analysis resulted in 3 critical components, namely sea water pump, heat exchanger and freshwater pump. The results of quantitative analysis of 3 critical components at RLLM = 0.6 between thetwo methods are not much different and error calculations have been carried out with RMSE, MAPE,and MAE with results close to 0. So, it can be seen that the MCS method can be applied to predictreliability values.